Dehumanization of Warfare Legal Implications of New Weapon Technologies - Heintschel von Heinegg, Wolff; Frau, Robert; Singer, Tassilo (Springer International Publishing : Imprint: Springer, 2018)
X, 233 p. 14 illus., 10 illus. in color.